2017
DOI: 10.3389/fpubh.2016.00290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Exercise as Evidence-Based Practice for Individuals with Autism Spectrum Disorder

Abstract: BackgroundThe purpose of this study was to conduct a systematic review of the literature to evaluate empirical support for the use of exercise as an evidence-based practice (EBP) for individuals with autism spectrum disorder (ASD), aged 1–21 years, using the Adapted Physical Activity Taxonomy (APAT) (1).MethodA systematic review of research, published within the past 10 years and accessible in SPORTDiscus, ProQuest Nursing, Science Direct, ERIC, Ovid MEDLINE, and PsychINFO databases, was conducted following se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
0
13
0
4
Order By: Relevance
“…Research on the benefits of specific PA interventions among adolescents with an ASD has shown improvements in behaviour, health and motor skills (Bremer et al 2016 ; Dillon et al 2016 ; Lang et al 2010 ; Sorensen and Zarrett 2014 ; Sowa and Meulenbroek 2012 ). The feelings of adolescents with an ASD about PA have been investigated through questionnaires and compared to typically developing adolescents, revealing both similarities, for example the enjoyment of PA and awareness of PA being “good for them”, and differences, such as lower enjoyment of group PA among adolescents with ASD compared to typically developing adolescents (Stanish et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the benefits of specific PA interventions among adolescents with an ASD has shown improvements in behaviour, health and motor skills (Bremer et al 2016 ; Dillon et al 2016 ; Lang et al 2010 ; Sorensen and Zarrett 2014 ; Sowa and Meulenbroek 2012 ). The feelings of adolescents with an ASD about PA have been investigated through questionnaires and compared to typically developing adolescents, revealing both similarities, for example the enjoyment of PA and awareness of PA being “good for them”, and differences, such as lower enjoyment of group PA among adolescents with ASD compared to typically developing adolescents (Stanish et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…tipados e repetitivos; com resistência a mudanças, incapacidade de desenvolver um contato olho a olho antes dos cinco anos de idade, e respostas anormais ao estímulo visual e auditivo. [1][2][3][4] Trata-se de disfunção psiconeurológica no desenvolvimento, no qual os déficits podem ser manifestados de forma leve, moderada e grave, e de acordo com alguns estudos, com incidência maior em crianças do sexo masculino do que feminino, com proporção de quatro indivíduos do sexo masculino para cada um do sexo feminino; quando ocorre em meninas, geralmente, os sinais e sintomas apresentam-se com um grau de severidade mais acentuado. 2,5,6 Com base no último relatório dos Centros para Controle e Prevenção de Doenças, um em cada 68 nascimentos foi uma criança autista nos Estados Unidos em 2014.…”
Section: Revista Saúde E Pesquisaunclassified
“…8 De acordo com a Associação Americana Psiquiátrica, em relação aos indivíduos diagnosticados com Transtorno do Espectro Autista (TEA), são caracterizados três níveis com base no suporte necessário: nível 1, exigindo suporte; nível 2, que requer apoio substancial; e nível 3, exigindo suporte extremo em todos os momentos. 1 A Educação Especial surgiu no final do século XVIII e início do XIX nos países escandinavos e América do Norte. No Brasil, desde o Império existiram instituições com educação caracterizada pela segregação.…”
Section: Revista Saúde E Pesquisaunclassified
See 1 more Smart Citation
“…Autism spectrum disorder (ASD) is a neurological disorder that is characterized by impairments in communication and social skills, and is associated with repetitive behavior and stereotypical movements (Dillon, Adams, Goudy, Bittner, & McNamara, 2017). Many children with ASD motor and sensory difficulties are observed (Baranek, 2002).…”
Section: Introductionmentioning
confidence: 99%